Temperate Bacteriophages (Prophages) in Pseudomonas aeruginosa Isolates Belonging to the International Cystic Fibrosis Clone (CC274) - Ambroa, Antón; Blasco, Lucia; López-Causapé, Carla; Trastoy, Rocio; Fernandez-García, Laura; Bleriot, Ines; Ponce-Alonso, Manuel; Pacios, Olga; López, Maria; Cantón, Rafael; Kidd, Timothy J.; Bou, German; et al. (Frontiers in Microbiology, 2020)
Bacteriophages are important in bacterial ecology and evolution. Pseudomonas aeruginosa is the most prevalent bacterial pathogen in chronic bronchopulmonary infection in cystic fibrosis (CF). In this study, we used bioinformatics, microbiological and microscopy techniques to analyse the bacteriophages present in 24 Pseudomonas aeruginosa isolates belonging to the international CF clone (ST274-CC274). Interestingly, we detected the presence of 5 members of the Inoviridiae family of prophages (Pf1, Pf4, Pf5, Pf6, Pf7), which have previously been observed in P. aeruginosa. In addition, we identified a new filamentous prophage, designated Pf8, in the P. aeruginosa AUS411.500 isolate belonging to the international CF clone. We detected only one prophage, never previously described, from the family Siphoviridiae (with 66 proteins and displaying homology with PHAGE_Pseudo_phi297_NC_016762). This prophage was isolated from the P. aeruginosa AUS531 isolate carrying a new gene which is implicated in the phage infection ability, named bci (Bacteriophage Control Infection). We characterized the role of the Bci protein in bacteriophage infection and in regulating the host Quorum Sensing (QS) system, motility and biofilm and pyocyanin production in the P. aeruginosa isogenic mutant AUS531∆bci isolate. The findings may be relevant for the identification of targets in the development of new strategies to control P. aeruginosa infections, particularly in CF patients.